Segmentation and fishery characteristics of the mixed-species multi-gear portuguese fleet - Duarte, Rafael (2018)
Fleet segmentation and knowledge of fishing fleet dynamics are essential to move from single species to fishery/fleet-based advice. The coastal mixed-species multi-gear Portuguese fleet comprises medium-sized (> 12m) vessels, using a diversity of passive gears, and is economically important. For hake (under a recovery plan) and monkfish (overexploited), it contributes > 50% to their total annuel landings. Commercial daily landings in 2005 from 271 vessels were analysed by region using non-hierarchical cluster analysis and multi-variate regression trees. The cluster analysis allowed the identification of regional fleet segments with a low mixture of species through-out the year. The multivariate regression trees were applied to clusters of vessels with a high mixture of species, to explain weekly landing profiles (species) by vessel technical characteristics, fishing license, and main landing port. The results showed a link between exploited species and geographic location, and in the north between vessel size and depth and an inshore/offshore range. Finally, from the analysis and for the most important species exploited by the Portuguese multi-gear fleet, it was possible to define two or three vessel groups that accounted for at least 50% of the landed value.